2016
DOI: 10.1177/0363546516651821
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcomes of a Symptom-Free Waiting Period After Sport-Related Concussion

Abstract: In comparison with prior published data collected from 1999 to 2004, utilization and duration of SFWPs were higher in the current study samples (99.3% vs 60.3% of athletes reported an SFWP; mean duration, 6.1 vs 3.2 days), and athletes were withheld from sports for more days than previously reported (12.3 vs 7.4 days). Rate of same-season repeat concussion was equivalent to that of prior published data. The findings support improved adherence to clinical management guidelines through increased utilization of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In contrast, only 5% of concussed players in CARE recovered within the first day, and nearly half of CARE athletes reported symptoms for more than 1 week after injury. Although our study does not allow us to directly determine the impact of specific educational initiatives targeted at college athletes during the 15-year interval between the NCAA Study and CARE,20 these findings further suggest that current-day athletes may be more aware of concussion symptoms and more likely to report their injury 26–28…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, only 5% of concussed players in CARE recovered within the first day, and nearly half of CARE athletes reported symptoms for more than 1 week after injury. Although our study does not allow us to directly determine the impact of specific educational initiatives targeted at college athletes during the 15-year interval between the NCAA Study and CARE,20 these findings further suggest that current-day athletes may be more aware of concussion symptoms and more likely to report their injury 26–28…”
Section: Discussionmentioning
confidence: 80%
“…Many researchers have examined total time loss, [4][5][6][7][19][20][21][22] yet distinct but related processes contribute to concussion recovery. Authors [4][5][6][7][19][20][21][22] assessing total time loss have evaluated the effects of predictors on symptom and RTAprotocol durations. This method of analysis may wash out the effects that are present in only the symptomatic and RTA-protocol periods.…”
Section: Discussionmentioning
confidence: 99%
“…If symptoms reemerge, the clinician reduces the athlete's physical exertion, and the protocol extends until the athlete can complete the prescribed physical activity without symptoms. 1 To date, most researchers [4][5][6][7] have investigated factors related to total time loss without assessing the 2 recovery subcomponents individually. Moreover, to our knowledge, no authors have examined factors associated with the duration of the RTA protocol.…”
mentioning
confidence: 99%
“…For most injured adult athletes, cognitive deficits, balance and symptoms improve rapidly during the first 2 weeks following injury . Some authors have suggested that the longer recovery times reported in more recent studies in part are due to changes in the medical management of concussion, with adoption of the gradual return to play recommendations from the Concussion in Sport Group statements . This topic was the subject of a recent detailed systematic review .…”
Section: Clinical Management In the Acute Stage Of Sports‐related Conmentioning
confidence: 99%